Implementasi Sistem Pencegahan Kecurangan Pelayanan Kesehatan Di Rumah Sakit Kota Prabumulih Pada Masa Pandemi Covid 19 - Fadliana Fathinuddin; Arief Wisnu Wardhana; Cholidi Zainuddin (Jurnal Jaminan Kesehatan Nasional, 2023)
Fraud in financing of health insurance is alleged to have burdened the cost of health services. The government issued Permenkes 16 of 2019 concerning prevention and handling of fraud and administrative sanctions against fraud in the implementation of JKN in an effort to prevent fraud. However, there is still potential for fraud to increase with pandemic conditions. This research aims to determine the implementation of the JKN Claim and Covid-19 Claim fraud prevention system and forms of fraud at the Prabumulih City Hospital during the Covid. This research can be useful theoretically and practically both in the field of health law politics and used by the Government, BPJS Health and Hospitals in an effort to improve fraud prevention system. The research method is empirical research with primary data sources from interviews with Prabumulih City Health Office, Prabumulih City Health BPJS and 4 Hospitals in Prabumulih. Results of the study shown that implementation of the fraud prevention system for health services at Prabumulih City Hospital during  Covid at the Health Service and BPJS Health KC Prabumulih was quite good, but in Prabumulih City Hospital  needed to be improved. Forms of fraud that can occur during the Covid-19 Pandemic at the Prabumulih City Hospital are fee contributions to participants for the Covid-19 antigen screening examination, extending the length of treatment for Covid-19 claims, submitting repeated claims to both JKN and covid claims and use the identity of another participant by not using the finger print in the participant's eligibility check.